A Systematic Literature Review on Early Warning Systems for Stock Market Crises: The Role of Investor Sentiment - Syarifuddin Rasyid; Darmawati; Ni Gusti Ayu Pitria; Fisca Mawa' Pangraran (Journal of Enterprise and Development (JED), 2024)
Purpose: This study systematically reviews existing research on early warning systems (EWS) for stock market crises, with a particular focus on the role of investor sentiment in enhancing prediction and mitigation efforts.Method: This study employed a systematic literature review (SLR) methodology, analyzing 32 peer-reviewed articles published between 2015 and 2024. The articles were sourced from reputable databases such as Scopus, EBSCO, and IEEE, ensuring a rigorous and reliable selection of relevant research.Result: The findings of this research indicate that investor sentiment significantly influences stock market dynamics and the occurrence of crises. The study emphasizes the importance of sentiment analysis in developing an early warning system (EWS) to enhance the accuracy and precision of stock market crisis predictions.Practical Implications for Economic Growth and Development: This research suggests that incorporating investor sentiment into early warning systems can enhance crisis prediction accuracy, stabilize financial markets, and guide proactive risk management for investors and policymakers.